Integrating Transcriptome-Wide Association Study and mRNA Expression Profiling Identifies Novel Genes Associated With Osteonecrosis of the Femoral Head - Ma, Mei; Li, Peilin; Liu, Li; Cheng, Shiqiang; Cheng, Bolun; Liang, Chu Jun; Tan, Sijia; Li, Wenyu; Wen, Yan; Guo, Xiong; Wu, Cuiyan (Frontiers in Genetics, 2021)
Objective This study aims to identify novel candidate genes associated with osteonecrosis of the femoral head (ONFH). Methods A transcriptome-wide association study (TWAS) was performed by integrating the genome-wide association study dataset of osteonecrosis (ON) in the UK Biobank with pre-computed mRNA expression reference weights of muscle skeleton (MS) and blood. The ON-associated genes identified by TWAS were further subjected to gene ontology (GO) analysis by the DAVID tool. Finally, a trans-omics comparative analysis of TWAS and genome-wide mRNA expression profiling was conducted to identify the common genes and the GO terms shared by both DNA-level TWAS and mRNA-level expression profile for ONFH. Results TWAS totally identified 564 genes that were with PTWAS value <0.05 for MS and blood, such as CBX1 (PTWAS = 0.0001 for MS), SRPK2 (PTWAS = 0.0002 for blood), and MYO5A (PTWAS = 0.0005 for blood). After comparing the genes detected by TWAS with the differentially expressed genes identified by mRNA expression profiling, we detected 59 overlapped genes, such as STEAP4 [PTWAS = 0.0270, FC (fold change)mRNA = 7.03], RABEP1 (PTWAS = 0.010, FCmRNA = 2.22), and MORC3 (PTWAS = 0.0053, FCmRNA = 2.92). The GO analysis of TWAS-identified genes discovered 53 GO terms for ON. Further comparing the GO results of TWAS and mRNA expression profiling identified four overlapped GO terms, including cysteine-type endopeptidase activity (PTWAS = 0.0006, PmRNA = 0.0227), extracellular space (PTWAS = 0.0342, PmRNA = 0.0012), protein binding (PTWAS = 0.0112, PmRNA = 0.0106), and ATP binding (PTWAS = 0.0464, PmRNA = 0.0033). Conclusion Several ONFH-associated genes and GO terms were identified by integrating TWAS and mRNA expression profiling. It provides novel clues to reveal the pathogenesis of ONFH.